Clinician's and women\'s perceptions of individual barriers for achieving a vaginal birth after cesarean (VBAC) in Iran: A qualitative content analysis - Robab latifnejade Roudsari; Mahboobeh Firoozi; Fatemeh Tara; Mohammad Reza Ahanchian (Babol University of Medical Sciences, 2020)
Background: High rate of repeat cesarean section and its complications are the results of cesarean tsunami in the last two decades in Iran. Vaginal birth after cesarean (VBAC) is an important alternative for repeat cesarean. However, the rate of VBAC in Iran is very low subject to some organizational and individual barriers is very low. This study explored the clinician's and women's perceptions of individual barriers to achieve VBAC. Methods: In this conventional content analysis, 28 semi-structured interviews and one focus group discussion was conducted with health care providers including gynecologists, midwives and family physicians as well as prior cesarean section mothers attended one of the women's hospitals in Mashhad, Iran in 2017. Participants were selected through purposive sampling considering the strategy of maximum variation. Data were analyzed according to Graneheim and Lundman (2004) method using MAXQDA.10 software. Results: The theme of "obstacles to acceptance and committed actions" emerged from two categories of "psychological barriers" and "operational barriers". Psychological barriers included 'sense of danger", "financial displeasure" and "negative attitude"; whereas, operational barriers consisted of 'barriers to decision making' and 'indolence'. Conclusion: Improving women's attitude via maternity care promotion, creating supportive environment, informing mothers about choice of birth mode and empowering them in shared decision making could influence women's VBAC request. Also organizing VBAC care team and creating motivations in medical team and hospital directors through reporting of research project outcomes on safety and benefits of VBAC could affect the VBAC rate.